1997
DOI: 10.1046/j.1471-4159.1997.68020855.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Characterization of Nitric Oxide Synthase in the Rat Suprachiasmatic Nucleus: Evidence for a Nitrergic Plexus in the Biological Clock

Abstract: Behavioral and electrophysiological evidence indicates that the biological clock in the hypothalamic suprachiasmatic nuclei (SCN) can be reset at night through release of glutamate from the retinohypothalamic tract and subsequent activation of nitric oxide synthase (NOS). However, previous studies using NADPH‐diaphorase staining or immunocytochemistry to localize NOS found either no or only a few positive cells in the SCN. By monitoring conversion of l‐[3H]arginine to l‐[3H]citrulline, this study demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
5
17
1
Order By: Relevance
“…Bands against neuronal NOS, a mediator of nighttime phase shifts induced by light (31), were evident at 155 kDa in SCN 2.2 extracts, consistent with SCN tissue and previous reports (Fig. 4A) (48). During the circadian night-phase, activation of heme oxygenase-2 (HO-2) mimics cGMP phase shifting and is downstream of acetylcholine signaling (49).…”
Section: Resultssupporting
confidence: 90%
“…Bands against neuronal NOS, a mediator of nighttime phase shifts induced by light (31), were evident at 155 kDa in SCN 2.2 extracts, consistent with SCN tissue and previous reports (Fig. 4A) (48). During the circadian night-phase, activation of heme oxygenase-2 (HO-2) mimics cGMP phase shifting and is downstream of acetylcholine signaling (49).…”
Section: Resultssupporting
confidence: 90%
“…Localization of the rat's M 1 •R expression by immunocytochemistry and in situ hybridization analysis includes neurons in the central area of the SCN (19). Thus, both proteins, M 1 •R and HO-2, are expressed in central SCN neurons, whereas nNOS expression in the central core area of the SCN is largely absent (5).…”
Section: Figmentioning
confidence: 98%
“…The distance this signal travels is apparently limited by the half-life of NO. Several studies have now shown that the enzyme responsible for the production of this gas, nitric oxide synthase (NOS), is present in the SCN and co-localized with VIP (70)(71)(72). Another population of NOS-immunoreactive cells is found among the glial fibrillary acidic protein (GFAP)-immunoreactive astrocytes (73).…”
Section: Gases: Nitric Oxidementioning
confidence: 99%